Steel sheets and press-molded products

By controlling the chemical composition and surface roughness of high-strength steel plates, ghostlines are suppressed, resulting in high-strength press-molded products with superior appearance quality for automotive components.

JP7623618B2Active Publication Date: 2025-01-29NIPPON STEEL CORPORATION
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2023543605
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-08-27
Publication Date
2025-01-29
Estimated Expiration
2041-08-27

Smart Images

  • Figure 0007623618000001
    Figure 0007623618000001
  • Figure 0007623618000002
    Figure 0007623618000002
Patent Text Reader

Abstract

This steel plate has: a chemical composition containing, by mass, 0.040-0.100% of C, 1.00-2.00% of Mn, 0.005-1.500% of Si, 0.100% or less of P, 0.0200% or less of S, 0.005-0.700% of Al, 0.0150% or less of N, and 0.0100% or less of O, the balance being Fe and impurities; and an arithmetic mean waviness Wa of 0.10-0.30 μm.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a steel sheet and a press-formed product. [Background technology]

[0002] From the viewpoint of protecting the global environment, there is a demand for lighter automobile bodies and improved collision safety. To meet these demands, efforts are being made to increase the strength and reduce the thickness of panel parts such as door outers. Unlike structural parts, these panel parts are visible to the public, so they require high appearance quality. Therefore, even high-strength steel sheets that have traditionally been used for structural parts are required to have excellent appearance quality after forming when used for panel parts.

[0003] One of the challenges to improve the appearance quality is to suppress the occurrence of ghost lines. Ghost lines are minute irregularities on the order of several mm that appear on the surface when a steel sheet having a hard phase and a soft phase is press-formed, as the area around the soft phase deforms preferentially. These irregularities appear as stripes on the surface, so press-formed products with ghost lines have poor appearance quality.

[0004] Patent Document 1 discloses a high-strength hot-dip galvanized steel sheet with excellent surface quality. Specifically, Patent Document 1 discloses a high-strength hot-dip galvanized steel sheet containing, by mass%, C: 0.02 to 0.20%, Si: 0.7% or less, Mn: 1.5 to 3.5%, P: 0.10% or less, S: 0.01% or less, Al: 0.1 to 1.0%, N: 0.010% or less, and Cr: 0.03 to 0.5%, and having a surface oxidation index A during annealing of 2.3 or more, defined by the formula A = 400Al / (4Cr + 3Si + 6Mn) in which the contents of Al, Cr, Si, and Mn are the same as those in the corresponding items, with the balance being Fe and unavoidable impurities, and further having a structure of the substrate consisting of ferrite and a second phase, the second phase being mainly martensite, and a hot-dip galvanized layer on the surface of the substrate.

[0005] Patent Document 2 discloses a hot-dip galvanized steel sheet having an Fe-Al alloy layer at the interface between a hot-dip galvanized layer and the base steel sheet, the Fe-Al alloy layer having an average thickness of 0.1 μm to 2.0 μm and a difference between the maximum thickness and the minimum thickness in the width direction of the steel sheet of 0.5 μm or less, and a refined layer directly in contact with the Fe-Al alloy layer, the difference between the maximum thickness and the minimum thickness of the refined layer in the width direction of the steel sheet of 2.0 μm or less.

[0006] Patent Document 3 discloses a high-strength thin steel plate characterized in that the Vickers hardness at a position 0.05 mm deep from the front and back surfaces of the steel plate is 100 to 250 Hv and is (Vickers hardness at a position 0.2 mm deep from the front and back surfaces) × 0.8 or less, the variation in Vickers hardness in an inner layer portion from a position 0.2 mm deep from the front and back surfaces toward the center of the plate thickness is 100 Hv or less, the inner layer portion contains bainite and martensite in a total area ratio of 80% or more, the surface roughness of the steel plate is 0.4 to 1.2 μm in terms of Ra, and the tensile strength of the steel plate is 780 MPa or more.

[0007] Patent Document 4 discloses a high-tensile galvannealed steel sheet characterized in that the galvannealed layer has a chemical composition containing, by mass%, 10 to 15% Fe and 0.20 to 0.45% Al, with the balance being Zn and impurities, and that the interfacial adhesion strength between the steel sheet and the galvannealed layer is 20 MPa or more.

[0008] Patent Document 5 discloses a high-strength steel sheet that is less susceptible to deterioration in properties after cutting, characterized in that the steel sheet structure is mainly composed of ferrite and bainite, the Mn segregation degree in the sheet thickness direction (= central Mn peak concentration / average Mn concentration) is 1.20 or less, and the maximum tensile strength is 540 MPa or more. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] Japanese Patent Publication No. 2005-220430 [Patent Document 2] International Publication No. 2019 / 026113 [Patent Document 3] Japanese Patent Publication No. 2006-70328 [Patent Document 4] Japanese Patent Publication No. 2006-97102 [Patent Document 5] Japanese Patent Publication No. 2009-263685 Summary of the Invention [Problem to be solved by the invention]

[0010] The present invention has been made in view of the above-mentioned circumstances. An object of the present invention is to provide a press-formed product having high strength and excellent appearance quality, and a steel sheet from which the press-formed product can be manufactured. [Means for solving the problem]

[0011] The gist of the present invention is as follows. (1) A steel sheet according to one embodiment of the present invention has a chemical composition, in mass%, C: 0.040~0.100%, Mn: 1.00-2.00%, Si: 0.005 to 1.500%, P: 0.100% or less, S: 0.0200% or less, Al: 0.005 to 0.700%, N: 0.0150% or less, O: 0.0100% or less, Cr: 0~0.80%, Mo: 0-0.16%, B: 0~0.0100%, Ti: 0 to 0.100%, Nb: 0 to 0.060%, V: 0 to 0.50%, Ni: 0 to 1.00%, Cu: 0-1.00%, W: 0 to 1.00%, Sn: 0-1.00%, Sb: 0 to 0.200%, Ca: 0 to 0.0100%, Mg: 0 to 0.0100%, Zr: 0 to 0.0100%, REM: 0 to 0.0100%, and The balance is Fe and impurities. The arithmetic mean waviness Wa is 0.10 to 0.30 μm. (2) The steel sheet according to the above (1) has a chemical composition, in mass%, Cr: 0.01 to 0.80%, Mo: 0.01 to 0.16%, B: 0.0001 to 0.0100%, Ti: 0.001 to 0.100%, Nb: 0.001 to 0.060%, V: 0.01 to 0.50%, Ni: 0.01 to 1.00%, Cu: 0.01 to 1.00%, W: 0.01 to 1.00%, Sn: 0.01 to 1.00%, Sb: 0.001 to 0.200%, Ca: 0.0001 to 0.0100%, Mg: 0.0001 to 0.0100%, Zr: 0.0001 to 0.0100%, and REM: 0.0001 to 0.0100% The resin may contain one or more selected from the group consisting of: (3) In the steel plate according to (1) or (2) above, an average value of Mn concentration in a region from a position 1 / 8 of the plate thickness from a surface of the steel plate in the plate thickness direction to a position 3 / 8 of the plate thickness from the surface in the plate thickness direction may be μ, and a standard deviation of the Mn concentration may be σ, where μ is an average value of the Mn concentration in a region from a position 1 / 8 of the plate thickness from the surface of the steel plate in the plate thickness direction, and σ is a standard deviation of the Mn concentration. (4) The steel sheet according to any one of the above (1) to (3) may have a decarburized layer having a thickness of 20 μm or more on a surface of the steel sheet. (5) The steel sheet according to any one of the above items (1) to (4) may have a plating layer on at least one surface of the steel sheet. (6) A press-formed product according to another aspect of the present invention is obtained by press forming the steel sheet according to any one of the above (1) to (5). Effect of the Invention

[0012] According to the above aspects of the present invention, it is possible to provide a press-formed product having high strength and excellent appearance quality, and a steel sheet from which this press-formed product can be manufactured. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The present inventors have studied a method for suppressing the occurrence of ghost lines after press forming of a high-strength steel sheet. As a result, the present inventors have found that it is effective to reduce the hardness difference in the steel and control the surface roughness of the steel sheet to a desired range. One of the factors that causes the hardness difference in the steel is band-shaped Mn segregation that occurs during the solidification process of the steel. When band-shaped Mn segregation occurs, the periphery of the part with high Mn concentration is likely to transform into austenite during annealing, so that after annealing after cold rolling, hard martensite occurs in a band shape. As a result, it is considered that the hardness difference in the steel becomes large, and ghost lines occur during press forming.

[0014] In general, it is considered that the smaller the surface roughness of the steel sheet used as a material, the better. If the surface roughness of the steel sheet is excessively large, the appearance quality is deteriorated. However, the present inventors have found that in order to suppress the occurrence of ghost lines in press-formed products, it is important to make the surface of the steel sheet used as a material appropriately rough without deteriorating the appearance quality.

[0015] The present invention has been made based on the above findings, and the steel sheet and press-formed product according to this embodiment will be described in detail below. However, the present invention is not limited to the configuration disclosed in this embodiment, and various modifications are possible without departing from the spirit of the present invention.

[0016] First, the chemical composition of the steel sheet according to this embodiment will be described. In the following, the numerical ranges described with "to" include the lower and upper limits. Numerical values ​​indicated as "less than" or "greater than" do not include the numerical range. In the following description, % regarding the chemical composition is mass % unless otherwise specified.

[0017] The chemical composition of the steel sheet according to this embodiment contains, in mass%, C: 0.040-0.100%, Mn: 1.00-2.00%, Si: 0.005-1.500%, P: 0.100% or less, S: 0.0200% or less, Al: 0.005-0.700%, N: 0.0150% or less, O: 0.0100% or less, and the balance: Fe and impurities. Each element will be described below.

[0018] C: 0.040~0.100% C is an element that increases the strength of steel sheets and press-formed products. To obtain a desired strength, the C content is set to 0.040% or more. To further increase the strength, the C content is preferably 0.050% or more, more preferably 0.060% or more, 0.070% or more, or 0.075% or more. Furthermore, by setting the C content to 0.100% or less, the diffusion of Mn during solidification is promoted, which makes it possible to suppress the occurrence of band-shaped Mn segregation. As a result, the occurrence of ghost lines after press forming can be suppressed. Therefore, the C content is set to 0.100% or less. The C content is preferably 0.095% or less, and more preferably 0.090% or less or 0.085% or less. When the Mn content is 1.40% or less, the C content is preferably more than 0.075%. By strictly controlling the Mn content and the C content in this way, Mn diffusion in the steel is promoted at high temperatures, and Mn segregation can be reduced.

[0019] Mn: 1.00-2.00% Mn is an element that improves the hardenability of steel and contributes to improving strength. In order to obtain a desired strength, the Mn content is set to 1.00% or more. The Mn content is preferably 1.05% or more, 1.10% or more, or 1.20% or more, more preferably 1.30% or more, 1.40% or more, or 1.50% or more. Furthermore, if the Mn content is 2.00% or less, the occurrence of band-shaped Mn segregation during the solidification of steel can be suppressed. Therefore, the Mn content is set to 2.00% or less. The Mn content is preferably 1.85% or less, more preferably 1.80% or less, and even more preferably 1.75% or less.

[0020] Silicon: 0.005 to 1.500% Silicon is an element that improves the balance between strength and formability of a steel sheet. To obtain this effect, the silicon content is set to 0.005% or more, and preferably 0.010% or more. In addition, Si is also an element that forms coarse Si oxides that act as the starting point of fracture. By setting the Si content to 1.500% or less, the formation of Si oxides can be suppressed, making it difficult for cracks to occur. As a result, embrittlement of the steel can be suppressed. Therefore, the Si content is set to 1.500% or less. The Si content is preferably 1.300% or less, and more preferably 1.000% or less.

[0021] P:0.100% or less P is an impurity element that embrittles steel. If the P content is 0.100% or less, the steel sheet can be prevented from becoming embrittled and prone to cracking during the production process. Therefore, the P content is set to 0.100% or less. From the viewpoint of productivity, the P content is preferably 0.050% or less, and more preferably 0.030% or less or 0.020% or less. Although the lower limit of the P content includes 0%, by setting the P content to 0.001% or more, the production costs can be further reduced, and therefore the P content may be set to 0.001% or more.

[0022] S: 0.0200% or less S is an impurity element that forms Mn sulfides and deteriorates the formability of steel sheet, such as ductility, hole expandability, stretch flangeability, and bendability. If the S content is 0.0200% or less, the formability of the steel sheet can be prevented from being significantly reduced. Therefore, the S content is set to 0.0200% or less. The S content is preferably 0.0100% or less, and more preferably 0.0080% or less. Although the lower limit of the S content includes 0%, by making the S content 0.0001% or more, the manufacturing costs can be further reduced, and therefore the S content may be set to 0.0001% or more.

[0023] Al: 0.005 to 0.700% Al is an element that functions as a deoxidizer. In order to obtain a sufficient deoxidizing effect of Al, the Al content is set to 0.005% or more. The Al content is preferably 0.010% or more or 0.025% or more. Furthermore, Al is an element that forms coarse oxides that act as starting points for fracture, embrittling steel. By setting the Al content to 0.700% or less, the generation of coarse oxides that act as starting points for fracture can be suppressed, and the tendency of the slab to crack can be suppressed. Therefore, the Al content is set to 0.700% or less. The upper limit of the Al content is preferably 0.600%, 0.400%, 0.200% or 100%, and more preferably 0.085%, 0.070%, 0.065% or 0.060%.

[0024] N: 0.0150% or less N is an impurity element that forms nitrides and deteriorates the formability of the steel sheet, such as ductility, hole expandability, stretch flangeability, and bendability. When the N content is 0.0150% or less, the formability of the steel sheet can be prevented from decreasing. Therefore, the N content is set to 0.0150% or less. N is also an element that causes welding defects during welding and inhibits productivity. Therefore, the N content is preferably 0.0120% or less, and more preferably 0.0100% or less. Although the lower limit of the N content includes 0%, by setting the N content to 0.0005% or more, the manufacturing costs can be further reduced, and therefore the N content may be set to 0.0005% or more.

[0025] O: 0.0100% or less O is an impurity element that forms oxides and inhibits formability such as ductility, hole expandability, stretch flangeability, and bendability of steel sheet. If the O content is 0.0100% or less, a significant decrease in formability of the steel sheet can be suppressed. Therefore, the O content is set to 0.0100% or less. It is preferably 0.0080% or less, and more preferably 0.0050% or less. Although the lower limit of the O content includes 0%, by setting the O content to 0.0001% or more, the production costs can be further reduced, and therefore the O content may be set to 0.0001% or more.

[0026] The steel sheet according to this embodiment may contain the following elements as optional elements in place of a portion of Fe. When the following optional elements are not contained, the content is 0%.

[0027] Cr: 0~0.80% Cr is an element that improves the hardenability of steel and contributes to improving the strength of steel plate. Since Cr is not necessarily contained, the lower limit of the Cr content includes 0%. In order to fully obtain the strength improving effect of Cr, the Cr content is preferably 0.01% or more, more preferably 0.20% or more, and even more preferably 0.30% or more. Furthermore, when the Cr content is 0.80% or less, the formation of coarse Cr carbides that may become the starting point of fracture can be suppressed. Therefore, the Cr content is set to 0.80% or less. In order to reduce the alloy cost, the upper limit of the Cr content may be set to 0.60%, 0.40%, 0.20%, 0.10%, or 0.05%, as necessary.

[0028] Mo: 0 to 0.16% Mo is an element that suppresses phase transformation at high temperatures and contributes to improving the strength of the steel sheet. Mo is not necessarily contained, so the lower limit of the Mo content includes 0%. In order to fully obtain the strength improving effect of Mo, the Mo content is preferably 0.01% or more, more preferably 0.05% or more, and even more preferably 0.10% or more. In addition, if the Mo content is 0.16% or less, the hot workability is deteriorated and the productivity is prevented from being deteriorated. Therefore, the Mo content is set to 0.16% or less. In order to reduce the alloy cost, the upper limit of the Mo content may be set to 0.12%, 0.10%, 0.08%, or 0.04%, as necessary. Incidentally, it is preferable to contain both 0.01 to 0.80% Cr and 0.01 to 0.16% Mo, since this can more reliably improve the strength of the steel sheet.

[0029] B: 0~0.0100% B is an element that suppresses phase transformation at high temperatures and contributes to improving the strength of the steel sheet. Since B is not necessarily contained, the lower limit of the B content includes 0%. In order to fully obtain the strength improving effect of B, the B content is preferably 0.0001% or more, more preferably 0.0005% or more, and even more preferably 0.0010% or more. Furthermore, if the B content is 0.0100% or less, the formation of B precipitates can be prevented, which can reduce the strength of the steel sheet. Therefore, the B content is set to 0.0100% or less. In order to reduce the alloy cost, the upper limit of the B content may be set to 0.0050%, 0.0030%, 0.0020%, 0.0010%, or 0.0005%, as necessary.

[0030] Ti: 0 to 0.100% Ti is an element that has the effect of reducing the amounts of S, N, and O that generate coarse inclusions that act as the starting points of fracture. Ti also has the effect of refining the structure and improving the strength-formability balance of the steel sheet. Since Ti is not necessarily contained, the lower limit of the Ti content includes 0%. In order to fully obtain the above effects, the Ti content is preferably 0.001% or more, and more preferably 0.001% or more. Furthermore, when the Ti content is 0.100% or less, the formation of coarse Ti sulfides, Ti nitrides, and Ti oxides can be suppressed, and the formability of the steel sheet can be ensured. Therefore, the Ti content is set to 0.100% or less. The Ti content is preferably set to 0.080% or less, and more preferably set to 0.060% or less. In order to reduce the alloy cost, the upper limit of the Ti content may be set to 0.040%, 0.020%, 0.010%, or 0.005%, as necessary.

[0031] Nb: 0 to 0.060% Nb is an element that contributes to improving the strength of steel sheets by strengthening with precipitates, by strengthening by grain refinement by inhibiting the growth of ferrite crystal grains, and by strengthening by dislocation by inhibiting recrystallization. Since Nb is not necessarily contained, the lower limit of the Nb content includes 0%. In order to fully obtain the above effects, the Nb content is preferably 0.001% or more, more preferably 0.005% or more, and even more preferably 0.010% or more. In addition, when the Nb content is 0.060% or less, recrystallization is promoted and the remaining non-recrystallized ferrite can be suppressed, and the formability of the steel sheet can be ensured. Therefore, the Nb content is set to 0.060% or less. The Nb content is preferably 0.050% or less, and more preferably 0.040% or less. In order to reduce the alloy cost, the upper limit of the Nb content may be set to 0.030%, 0.020%, 0.010%, or 0.005%, as necessary.

[0032] V: 0~0.50% V is an element that contributes to improving the strength of steel sheets by strengthening with precipitates, strengthening by grain refinement by inhibiting the growth of ferrite crystal grains, and strengthening by dislocation by inhibiting recrystallization. V is not necessarily contained, so the lower limit of the V content includes 0%. In order to fully obtain the strength improving effect of V, the V content is preferably 0.01% or more, and more preferably 0.03% or more. Furthermore, when the V content is 0.50% or less, a large amount of carbonitrides is precipitated, which can prevent the formability of the steel sheet from being deteriorated. Therefore, the V content is set to 0.50% or less. In order to reduce the alloy cost, the upper limit of the V content may be set to 0.30%, 0.20%, 0.10%, 0.05%, or 0.02%, as necessary.

[0033] Ni: 0 to 1.00% Ni is an element that suppresses phase transformation at high temperatures and contributes to improving the strength of the steel sheet. Since Ni is not necessarily contained, the lower limit of the Ni content includes 0%. In order to fully obtain the strength improving effect of Ni, the Ni content is preferably 0.01% or more, more preferably 0.05% or more, and even more preferably 0.20% or more. In addition, when the Ni content is 1.00% or less, the deterioration of the weldability of the steel sheet can be suppressed. Therefore, the Ni content is set to 1.00% or less. In order to reduce the alloy cost, the upper limit of the Ni content may be set to 0.60%, 0.40%, 0.20%, 0.10%, or 0.03%, as necessary.

[0034] Cu: 0-1.00% Cu is present in steel in the form of fine particles and is an element that contributes to improving the strength of the steel sheet. Cu is not necessarily contained, so the lower limit of the Cu content includes 0%. In order to fully obtain the strength improving effect of Cu, the Cu content is preferably 0.01% or more, more preferably 0.05% or more, and even more preferably 0.15% or more. In addition, when the Cu content is 1.00% or less, the deterioration of the weldability of the steel sheet can be suppressed. Therefore, the Cu content is set to 1.00% or less. In order to reduce the alloy cost, the upper limit of the Cu content may be set to 0.60%, 0.40%, 0.20%, 0.10%, or 0.03%, as necessary.

[0035] W:0~1.00% W is an element that suppresses phase transformation at high temperatures and contributes to improving the strength of the steel sheet. Since W is not necessarily contained, the lower limit of the W content includes 0%. In order to fully obtain the strength improving effect of W, the W content is preferably 0.01% or more, more preferably 0.03% or more, and even more preferably 0.10% or more. In addition, if the W content is 1.00% or less, the hot workability is deteriorated and the productivity is prevented from being deteriorated. Therefore, the W content is set to 1.00% or less. In order to reduce the alloy cost, the upper limit of the W content may be set to 0.50%, 0.20%, 0.10%, 0.05%, or 0.02%, as necessary.

[0036] Sn: 0 to 1.00% Sn is an element that suppresses the coarsening of crystal grains and contributes to improving the strength of the steel sheet. Since Sn is not necessarily contained, the lower limit of the Sn content includes 0%. In order to fully obtain the effect of Sn, the Sn content is more preferably 0.01% or more. Furthermore, if the Sn content is 1.00% or less, the steel sheet can be prevented from becoming embrittled and breaking during rolling. Therefore, the Sn content is set to 1.00% or less. In order to reduce alloy costs, the upper limit of the Sn content may be set to 0.50%, 0.20%, 0.10%, 0.05%, or 0.02%, as necessary.

[0037] Sb: 0 to 0.200% Sb is an element that suppresses the coarsening of crystal grains and contributes to improving the strength of the steel sheet. Since Sb is not necessarily contained, the lower limit of the Sb content includes 0%. In order to fully obtain the above effects, the Sb content is preferably 0.001% or more, and more preferably 0.005% or more. Furthermore, if the Sb content is 0.200% or less, the steel sheet can be prevented from becoming embrittled and breaking during rolling. Therefore, the Sb content is set to 0.200% or less. In order to reduce alloy costs, the upper limit of the Sb content may be set to 0.100%, 0.070%, 0.040%, 0.010%, or 0.005%, as necessary.

[0038] Ca: 0 to 0.0100% Magnesium: 0 to 0.0100% Zr: 0 to 0.0100% REM: 0~0.0100% Ca, Mg, Zr and REM are elements that contribute to improving the formability of steel sheet. Ca, Mg, Zr and REM are not necessarily contained, so the lower limit of the total content of these elements includes 0%. In order to fully obtain the formability improvement effect, the content of each of these elements is preferably 0.0001% or more, and more preferably 0.0010% or more. In order to fully obtain the above effect, it is not necessary to contain all of the above elements, and it is sufficient that the content of any one of them is 0.0001% or more. In addition, when the content of each of Ca, Mg, Zr and REM is 0.0100% or less, the decrease in ductility of the steel sheet can be suppressed. Therefore, the content of each of these elements is set to 0.0100% or less. It is preferably set to 0.0050% or less. In order to reduce the alloy cost, the upper limit of the content of each of Ca, Mg, Zr and REM may be set to 0.0030%, 0.0020%, 0.0010% or 0.0003%, respectively, as necessary. REM (Rare Earth Metal) refers to a total of 17 elements consisting of Sc, Y and lanthanides, and the REM content refers to the total content of these elements.

[0039] The balance of the chemical composition of the steel sheet according to the present embodiment may be Fe and impurities. Examples of impurities include elements that are inevitably mixed in from steel raw materials or scrap and / or during the steelmaking process, and elements that are allowed to be present within a range that does not impair the properties of the steel sheet according to the present embodiment. Examples of impurities include H, Na, Cl, Co, Zn, Ga, Ge, As, Se, Y, Tc, Ru, Rh, Pd, Ag, Cd, In, Te, Cs, Ta, Re, Os, Ir, Pt, Au, Pb, Bi, and Po. The total amount of impurities may be 0.100% or less.

[0040] The chemical composition of the steel sheet may be measured by a general analytical method. For example, it may be measured by ICP-AES (Inductively Coupled Plasma-Atomic Emission Spectrometry). C and S may be measured by the combustion-infrared absorption method, N by the inert gas fusion-thermal conductivity method, and O by the inert gas fusion-non-dispersive infrared absorption method. When the steel sheet has a plating layer on the surface, the plating layer on the surface may be removed by mechanical grinding before the chemical composition is analyzed.

[0041] Arithmetic mean waviness Wa: 0.10~0.30μm In general, the smaller the arithmetic mean waviness Wa of the steel sheet material, the more preferable it is in terms of appearance quality. However, the present inventors have found that in order to suppress the occurrence of ghost lines in press-formed products, the surface of the steel sheet material is appropriately roughened, specifically, the arithmetic mean waviness Wa is set to 0.10 μm or more. Therefore, in the steel sheet according to this embodiment, the arithmetic mean waviness Wa is set to 0.10 μm or more. It is preferably 0.13 μm or more. Moreover, if the arithmetic mean waviness Wa is excessively large, the appearance quality of the steel sheet itself deteriorates, and the poor appearance quality is maintained even after press forming. Therefore, the arithmetic mean waviness Wa is set to 0.30 μm or less, and preferably 0.25 μm or less.

[0042] The arithmetic mean waviness Wa refers to the arithmetic mean waviness of a steel sheet when the steel sheet does not have a plating layer, and refers to the arithmetic mean waviness of the plating layer when the steel sheet has a plating layer on its surface.

[0043] In this embodiment, the arithmetic mean waviness Wa is obtained by the following method. A 50mm x 50mm test piece is cut out from a position 10mm or more away from the end face of the steel plate. Next, a laser displacement measuring device (Keyence VK-X1000) is used to measure three lines of the profile along a direction perpendicular to the rolling direction. From the obtained results, a waviness curve is obtained by sequentially applying a profile curve filter with cutoff values ​​λc and λf to the cross-sectional curve in accordance with JIS B 0601:2013. Specifically, from the obtained measurement results, components with wavelengths λc of 0.8mm or less and components with wavelengths λf of 2.5mm or more are removed to obtain a waviness curve. Based on the obtained waviness curve, an arithmetic mean waviness is calculated in accordance with JIS B 0601:2013, and the average value of the total three lines is calculated. The arithmetic mean of the average values ​​of the calculated three lines is taken as the arithmetic mean waviness Wa of the steel plate. When the steel sheet has a plating layer on the surface, the above-mentioned line analysis may be carried out on the surface of the plating layer.

[0044] (3σ / μ)×100≦7.0 In the steel sheet according to the present embodiment, when the average value of the Mn concentration in the region from a position 1 / 8 of the thickness from the surface of the steel sheet in the thickness direction to a position 3 / 8 of the thickness from the surface in the thickness direction (the region from 1 / 8 depth from the surface of the steel sheet to 3 / 8 depth from the surface of the steel sheet) is μ in unit mass %, and the standard deviation of the Mn concentration is σ in unit mass %, it is preferable that (3σ / μ)×100≦7.0. By making (3σ / μ)×100 7.0 or less, the occurrence of Mn segregation in the steel sheet can be further reduced, the occurrence of ghost lines can be further suppressed, and a press-formed product with better appearance quality can be obtained. It is more preferable that (3σ / μ)×100 is 6.5 or less. The lower limit of (3σ / μ)×100 is not particularly limited, but may be 0. Since the manufacturing cost increases in order to reduce (3σ / μ)×100, the lower limit may be 2.0, 4.0, or 5.0. If necessary, the upper limit of (3σ / μ)×100 may be set to 11.0, 10.0, 9.0, or 8.0.

[0045] In this embodiment, the average value μ of the Mn concentration and the standard deviation σ of the Mn concentration are obtained by the following method. After mirror polishing the thickness cross section of the steel plate, the Mn concentration is measured at 600 points at a predetermined depth position with a measurement interval of 1 μm in the rolling direction of the steel plate. The Mn concentration (mass%) at the predetermined depth position is obtained by calculating the average value of the obtained Mn concentrations. This operation is performed every 1 μm in the thickness direction, from a position 1 / 8 of the thickness from the surface of the steel plate in the thickness direction to a position 3 / 8 of the thickness from the surface in the thickness direction. The average value (arithmetic mean) of all the obtained Mn concentrations is calculated to obtain the average value μ of the Mn concentration. In addition, the standard deviation of all the obtained Mn concentrations is calculated to obtain the standard deviation σ of the Mn concentration. The apparatus used is an electron probe microanalyzer (EPMA), and the measurement conditions are an accelerating voltage of 15 kV.

[0046] The steel sheet according to the present embodiment may have a plating layer on at least one surface of the steel sheet. Examples of the plating layer include a zinc plating layer, a zinc alloy plating layer, and a zinc alloy plating layer obtained by subjecting these to an alloying treatment.

[0047] The zinc plating layer and zinc alloy plating layer are formed by hot-dip plating, electroplating, or vapor deposition plating. When the Al content of the zinc plating layer is 0.5 mass% or less, sufficient adhesion between the surface of the steel sheet and the zinc plating layer can be ensured, so the Al content of the zinc plating layer is preferably 0.5 mass% or less. When the zinc-plated layer is a hot-dip galvanized layer, the Fe content of the hot-dip galvanized layer is preferably 3.0 mass % or less in order to improve the adhesion between the steel sheet surface and the zinc-plated layer. When the zinc plating layer is an electrolytic zinc plating layer, the Fe content of the electrolytic zinc plating layer is preferably 0.5 mass % or less from the viewpoint of improving corrosion resistance.

[0048] The zinc plating layer and zinc alloy plating layer may contain one or more of Al, Ag, B, Be, Bi, Ca, Cd, Co, Cr, Cs, Cu, Ge, Hf, Zr, I, K, La, Li, Mg, Mn, Mo, Na, Nb, Ni, Pb, Rb, Sb, Si, Sn, Sr, Ta, Ti, V, W, Zr, and REM, to the extent that the corrosion resistance and formability of the steel sheet are not impaired. In particular, Ni, Al, and Mg are effective in improving the corrosion resistance of the steel sheet.

[0049] The zinc plating layer or zinc alloy plating layer may be a zinc alloy plating layer or zinc alloy plating layer that has been subjected to an alloying treatment. When the hot-dip galvanizing layer or hot-dip zinc alloy plating layer is subjected to an alloying treatment, the Fe content of the hot-dip galvanizing layer (galvannealed layer) or hot-dip zinc alloy plating layer (alloyed zinc alloy plating layer) after the alloying treatment is preferably 7.0 to 13.0 mass% from the viewpoint of improving the adhesion between the steel sheet surface and the alloying plating layer. By subjecting a steel sheet having a hot-dip galvanizing layer or hot-dip zinc alloy plating layer to an alloying treatment, Fe is taken into the plating layer, and the Fe content increases. This allows the Fe content to be 7.0 mass% or more. That is, a zinc plating layer having an Fe content of 7.0 mass% or more is a zinc alloy plating layer or zinc alloy plating layer.

[0050] The Fe content in the plating layer can be obtained by the following method. Only the plating layer is dissolved and removed using a 5 volume % HCl aqueous solution containing an inhibitor. The Fe content in the resulting solution is measured using ICP-AES (Inductively Coupled Plasma-Atomic Emission Spectrometry) to obtain the Fe content (mass%) in the plating layer.

[0051] The steel sheet according to this embodiment may have a decarburized layer having a thickness of 20 μm or more on the surface of the steel sheet, regardless of the presence or absence of a plating layer. By making the thickness of the decarburized layer 20 μm or more, band-shaped Mn segregation that causes streaks is reduced, and the appearance quality after press forming is further improved.

[0052] In this embodiment, the thickness of the decarburized layer is measured by the following method. For three randomly selected locations on a steel plate, the carbon concentration is measured every 1 μm in the area from the surface of the steel plate to a position half the plate thickness in the depth direction (plate thickness direction). The area with a carbon concentration half or less of the carbon concentration at a position half the plate thickness from the surface is regarded as the decarburized layer, and the thickness of the decarburized layer is obtained by calculating the thickness of the area. For the measurements, a Marcus type high frequency glow discharge optical emission surface analyzer (GD-Profiler) manufactured by Horiba, Ltd. is used.

[0053] The thickness of the steel plate according to the present embodiment is not limited to a specific range, but is preferably 0.2 to 2.0 mm in consideration of versatility and manufacturability. By making the thickness 0.2 mm or more, it becomes easy to maintain the shape of the steel plate flat, and the dimensional accuracy and shape accuracy can be improved. Therefore, the thickness is preferably 0.2 mm or more. More preferably, it is 0.4 mm or more. On the other hand, if the sheet thickness is 2.0 mm or less, it becomes easy to apply appropriate strain and control the temperature during the manufacturing process, and a homogeneous structure can be obtained. Therefore, the sheet thickness is preferably 2.0 mm or less, and more preferably 1.5 mm or less.

[0054] The steel sheet according to the present embodiment preferably has a tensile strength of 500 to 750 MPa. By setting the tensile strength to 500 MPa or more, the steel sheet can be suitably applied to panel-related parts. By setting the tensile strength to 750 MPa or less, the press formability can be improved and deterioration of appearance quality due to the occurrence of ghost lines can be suppressed. The lower limit of the tensile strength may be 540 MPa, 580 MPa, or 600 MPa, and the upper limit may be 680 MPa or 660 MPa.

[0055] The tensile strength is evaluated in accordance with JIS Z 2241:2011. The test piece is No. 5 test piece of JIS Z 2241:2011. The tensile test piece is taken from the 1 / 4 part from the end in the plate width direction, and the direction perpendicular to the rolling direction is the longitudinal direction.

[0056] Next, a press-formed product according to the present embodiment that can be manufactured by press-forming the above-mentioned steel sheet will be described. The press-formed product according to the present embodiment has the same chemical composition as the above-mentioned steel sheet. The press-formed product according to the present embodiment may also have the above-mentioned plating layer on at least one surface.

[0057] Since the press-formed product according to the present embodiment is obtained by press-forming the above-mentioned steel sheet, the occurrence of ghost lines is suppressed, and the quality of the appearance is excellent. Specific examples of the press-formed product include panel parts such as door outers of automobile bodies.

[0058] In the press molded product according to this embodiment, excellent appearance quality means that stripes (i.e. ghost lines) on the surface spaced at intervals of the order of several millimeters are not observed. In other words, the maximum length of stripes spaced at intervals of the order of several millimeters that are observed when an arbitrary area of ​​100 mm x 100 mm is visually inspected is 50 mm or less. The maximum length of the stripes is preferably 20 mm or less. It is more preferable that no stripes are observed at all.

[0059] In the press-molded product according to this embodiment, the occurrence of ghost lines is suppressed, so that the sum Wz of the maximum peak height Zp and the maximum valley height Zv of the waviness curve is 0.60 μm or less. Furthermore, by manufacturing a press-formed product using a steel sheet with a suitably controlled 3σ / μ, it is possible to obtain a press-formed product with superior appearance quality, that is, a press-formed product having a sum Wz of the maximum peak height Zp and the maximum valley height Zv of the waviness curve of 0.40 μm or less can be obtained. Wz is obtained in accordance with JIS B 0601:2013 by obtaining the waviness curve of the surface of the press-formed product, determining the maximum peak height Zp and the maximum valley height Zv, and calculating the sum of these.

[0060] Next, a method for manufacturing a steel sheet according to this embodiment will be described. The steel sheet according to the present embodiment can obtain the effect as long as it has the above-mentioned characteristics, regardless of the manufacturing method. Also, instead of a steel sheet, a steel strip may be used. However, by using a steel having the above-mentioned chemical composition, for example, by controlling the following conditions (I) to (IV) in a composite and inseparable manner, a steel sheet having a favorably controlled arithmetic mean waviness Wa can be stably manufactured. In order to favorably control 3σ / μ, it is preferable to further control condition (V) in addition to the following conditions (I) to (IV). In order to favorably control the thickness of the decarburized layer, it is preferable to further control condition (VI) in addition to the following conditions (I) to (IV). Note that conditions (V) and (VI) are optional conditions. Each condition will be explained below.

[0061] (I) The coiling temperature is 550°C or higher. (II) The pickling time is 50 seconds or more. (III) The arithmetic mean roughness Ra of the rolling roll surface in the final pass of cold rolling is 0.2 to 0.7 μm. (IV) The reduction rate of the temper rolling is set to 0.3 to 0.7%, and the arithmetic mean roughness Ra of the rolling roll is set to 1.5 to 3.5 μm. (V) Heat the slab to a temperature range of 1200°C or higher and hold it at that temperature range for 5 hours or more. (VI) Annealing is performed with a dew point (average dew point inside the annealing furnace) of -20°C or higher and a residence time of the steel sheet in a temperature range of 700°C or higher of 50 to 400 seconds.

[0062] (I) Winding temperature: 550°C or higher By setting the coiling temperature after hot rolling to a high temperature range of 550°C or higher, scale is likely to be generated on the surface of the steel sheet. As a result, unevenness is likely to be generated on the surface of the steel sheet after pickling. The coiling temperature is more preferably 600°C or higher, and even more preferably 650°C or higher.

[0063] (II) Pickling time: 50 seconds or more In the pickling after coiling and before cold rolling, if the pickling time is 50 seconds or more, unevenness tends to occur on the surface of the steel sheet, and the pickling time is more preferably 70 seconds or more.

[0064] (III) Arithmetic mean roughness Ra of the rolling roll in the final pass of cold rolling: 0.2 to 0.7 μm By setting the arithmetic mean roughness Ra of the rolling roll surface in the final pass in cold rolling after pickling to 0.2 to 0.7 μm, it is possible to form appropriate irregularities on the surface of the steel sheet during cold rolling. It is more preferable that the arithmetic mean roughness Ra of the rolling roll is 0.3 μm or more.

[0065] Since ordinary rolling rolls do not have the above-mentioned arithmetic mean roughness Ra, the steel sheet according to the present embodiment cannot be manufactured. In order to manufacture the steel sheet according to the present embodiment, it is desirable to use special rolling rolls in the final pass of cold rolling.

[0066] (IV) Reduction rate of temper rolling: 0.3 to 0.7%, arithmetic mean roughness Ra of rolling roll: 1.5 to 3.5 μm In temper rolling after annealing (or after plating in the case of a plated material), the reduction is set to 0.3 to 0.7% and the arithmetic mean roughness Ra of the rolling roll surface is set to 1.5 to 3.5 μm, so that unevenness can be formed on the surface of the steel sheet. It is more preferable that the reduction during temper rolling is 0.5% or more and the arithmetic mean roughness Ra of the rolling roll surface is 2.3 μm or more.

[0067] (V) Slab heating temperature and holding time: 1200℃ or higher for 5 hours or more Condition (V) is an optional condition. By heating the slab in a temperature range of 1200°C or higher for 5 hours or more, it is possible to preferably control 3σ / μ in the region from a position 1 / 8 of the plate thickness from the surface of the steel plate in the plate thickness direction to a position 3 / 8 of the plate thickness from the surface in the plate thickness direction (region from 1 / 8 depth from the surface of the steel plate to 3 / 8 depth from the surface of the steel plate). As a result, it is possible to further reduce the occurrence of Mn segregation in the steel plate, and it is possible to obtain a press-formed product with better appearance quality.

[0068] (VI) Dew point: -20°C or higher, residence time of steel sheet in temperature range of 700°C or higher: 50 to 400 seconds Condition (VI) is an optional condition. In this embodiment, the steel sheet after cold rolling obtained by the above-mentioned method may be annealed. The dew point during annealing (average dew point in the annealing furnace) is set to -20°C or higher, and the residence time of the steel sheet in a temperature range of 700°C or higher is set to 50 to 400 seconds, so that the surface of the steel sheet can be stably decarburized. This makes it possible to form a decarburized layer having a thickness of 30 μm or more on the surface of the steel sheet. The upper limit of the dew point does not need to be particularly set, but may be about 10°C.

[0069] Other than the above-mentioned conditions, there are no particular limitations, but it is preferable to satisfy, for example, the following conditions. The steel slab is heated to a temperature range of 1100°C or higher, and then hot-rolled. After hot rolling, coiling is performed, and then pickling is performed. After pickling, cold rolling is performed. The cumulative reduction in cold rolling is preferably 30 to 90%. After cold rolling, annealing is performed. Then, if necessary, the above-mentioned plating layer is formed. It is also preferable to perform temper rolling after that.

[0070] Next, a method for manufacturing a press-formed product according to this embodiment will be described. The press forming method is not particularly limited. For example, panel parts of an automobile such as a door outer can be formed by pressing a steel sheet with a blank holder and a die, and then applying a strain to the steel sheet by pressing a punch against it, thereby stretching it. This type of forming is called drawing forming or stretch forming. EXAMPLES

[0071] Next, an embodiment of the present invention will be described. The conditions in the embodiment are an example of conditions adopted to confirm the feasibility and effects of the present invention. The present invention is not limited to this example of conditions. Various conditions may be adopted in the present invention as long as they do not deviate from the gist of the present invention and achieve the object of the present invention.

[0072] Steel having the chemical composition shown in Table 1 was melted and continuously cast into slabs with a thickness of 240 to 300 mm. The obtained slabs were used to produce cold-rolled steel sheets and plated steel sheets under the conditions (I) to (V) described below. In Table 2, if a condition was satisfied, "OK" was entered in the column for that condition, and if a condition was not satisfied, "NG" was entered in the column for that condition. The sheet thicknesses of the obtained steel sheets and plated steel sheets were 0.2 to 2.0 mm.

[0073] In addition, annealing was performed after the cold rolling.

[0074] The manufacturing conditions other than conditions (I) to (VI) were as follows. The slab was heated to a temperature range of 1100°C or higher, and then hot-rolled. After hot-rolling, coiling was performed, and then pickling was performed. After pickling, cold rolling was performed with a cumulative reduction of 30 to 90%. After cold rolling, annealing was performed, and a galvannealed layer (GA), a galvannealed layer (GI), and an electroplated layer (EG) were formed as necessary. Then, temper rolling was performed.

[0075] The conditions (I) to (VI) in the table are as follows. (I) The coiling temperature is 550°C or higher. (II) The pickling time is 50 seconds or more. (III) The arithmetic mean roughness Ra of the rolling roll surface in the final pass of cold rolling is 0.2 to 0.7 μm. (IV) The reduction rate of the temper rolling is set to 0.3 to 0.7%, and the arithmetic mean roughness Ra of the rolling roll is set to 1.5 to 3.5 μm. (V) Heat the slab to a temperature range of 1200°C or higher and hold it at that temperature range for 5 hours or more. (VI) Annealing is performed with a dew point (average dew point inside the annealing furnace) of -20°C or higher and a residence time of the steel sheet in a temperature range of 700°C or higher of 50 to 400 seconds.

[0076] Next, the manufactured steel sheet and plated steel sheet were used to manufacture a roughly semi-cylindrical simulated part (press-formed product) simulating a door outer by press forming. When press forming this simulated part, the material (steel sheet or plated steel sheet) was actively flowed into a die so that at any position on the surface of the simulated part, the ratio of the strain in any direction along the surface of the simulated part to the strain in that direction (any direction) was about 1. In other words, press forming was performed so that no anisotropy of strain would occur at any position on the surface of the simulated part.

[0077] For the obtained steel sheets and plated steel sheets, the arithmetic mean waviness Wa, the mean value μ and standard deviation σ of the Mn concentration, the tensile strength, and the thickness of the decarburized layer were determined by the above-mentioned methods.

[0078] When the obtained tensile strength was 500 MPa or more, it was judged to have high strength and to pass the test, whereas when the obtained tensile strength was less than 500 MPa, it was judged to have poor strength and to fail the test.

[0079] The appearance quality of the simulated parts was evaluated by the following method. The appearance quality was evaluated based on the degree of ghost lines that appeared on the surface of the mock parts after molding. The surface after press molding was ground with a grindstone, and stripes that appeared on the surface at intervals of several millimeters were judged to be ghost lines, and were scored from 1 to 5 depending on the degree of the stripes. An arbitrary area of ​​100 mm x 100 mm was visually inspected, and if no stripes were found, it was scored as "1", if the maximum length of the stripes was 20 mm or less, it was scored as "2", if the maximum length of the stripes was more than 20 mm and less than 50 mm, it was scored as "3", if the maximum length of the stripes was more than 50 mm and less than 70 mm, it was scored as "4", and if the maximum length of the stripes was more than 70 mm, it was scored as "5". If the evaluation was "3" or less, the appearance quality was deemed excellent and the mock parts were judged to pass. On the other hand, if the evaluation was "4" or more, the appearance quality was deemed to be poor and the mock parts were judged to fail.

[0080] Furthermore, the appearance quality was evaluated more strictly by "Wz, which is the sum of the maximum peak height Zp and the maximum valley height Zv of the waviness curve." Using the same method as when determining the arithmetic mean waviness Wa, a waviness curve of the surface of the press-molded product (simulated part) was obtained in accordance with JIS B 0601:2013. From this waviness curve, the maximum peak height Zp and the maximum valley height Zv were obtained, and Wz was obtained by calculating the sum of these. If the obtained Wz was 0.40 μm or less, it was determined that the appearance quality was superior.

[0081] [Table 1]

[0082] [Table 2]

[0083] From Table 2, it can be seen that the press-formed products according to the examples of the present invention have high strength and excellent appearance quality. It can also be seen that the steel sheets according to the examples of the present invention were able to produce press-formed products having high strength and excellent appearance quality. Furthermore, it can be seen that the examples of the present invention, in which 3σ / μ was 7.0 or less, had better appearance quality after press forming.

[0084] On the other hand, it is seen that the press-formed products according to the comparative examples had poor strength or deteriorated appearance quality. It is also seen that the steel sheets according to the comparative examples were not able to produce press-formed products having high strength and excellent appearance quality. [Industrial Applicability]

[0085] According to the above aspects of the present invention, it is possible to provide a press-formed product having high strength and excellent appearance quality, and a steel sheet from which this press-formed product can be manufactured.

Claims

1. The chemical composition, in mass%, is C: 0.040-0.100%, Mn: 1.00-2.00%, Si: 0.005-1.500%, P: 0.100% or less, S: 0.0200% or less, Al: 0.005-0.700%, N: 0.0150% or less, O: 0.0100% or less, Cr: 0-0.80%, Mo: 0 to 0.16%, B: 0 to 0.0100%, Ti: 0 to 0.100%, Nb: 0 to 0.060%, V: 0 to 0.50%, Ni: 0 to 1.00%, Cu: 0 to 1.00%, W: 0-1.00%, Sn: 0-1.00%, Sb: 0 to 0.200%, Ca: 0-0.0100%, Mg: 0 to 0.0100%, Zr: 0 to 0.0100%, REM: 0 to 0.0100%, and The balance is Fe and impurities. A steel sheet having an arithmetic mean waviness Wa of 0.10 to 0.30 μm.

2. The chemical composition, in mass%, Cr: 0.01-0.80%, Mo: 0.01-0.16%, B: 0.0001 to 0.0100%, Ti: 0.001 to 0.100%, Nb: 0.001-0.060%, V: 0.01 to 0.50%, Ni: 0.01-1.00%, Cu: 0.01 to 1.00%, W: 0.01-1.00%, Sn: 0.01-1.00%, Sb: 0.001-0.200%, Ca: 0.0001-0.0100%, Mg: 0.0001-0.0100%, Zr: 0.0001 to 0.0100%, and REM: 0.0001~0.0100% The steel sheet according to claim 1, further comprising one or more selected from the group consisting of:

3. The steel sheet according to claim 1 or 2, characterized in that, when an average value of Mn concentration in a region from a position 1 / 8 of the sheet thickness from a surface of the steel sheet in the sheet thickness direction to a position 3 / 8 of the sheet thickness from the surface in the sheet thickness direction is μ and a standard deviation of the Mn concentration is σ, (3σ / μ)×100≦7.

0.

4. The steel plate according to any one of claims 1 to 3, characterized in that the surface of the steel plate has a decarburized layer having a thickness of 20 µm or more.

5. The steel sheet according to any one of claims 1 to 4, characterized in that the steel sheet has a plating layer on at least one surface thereof.

6. A press-formed product, characterized in that it is obtained by press-forming the steel sheet according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Specular picture panel and manufacture thereof

    JP1995008362A

  • Method and apparatus for producing cold rolled sheet metal or strip and the resulting sheet metal or strip

    JP1997502661A

  • Steel sheet excellent in external appearance of panel and dent resistance after panel working

    JP1998046289A

  • Cold-rolled steel sheet and galvanized steel sheet excellent in panel surface shape and dent resistance, and their manufacture

    JP1998324953A

  • High strength hot dip galvanized steel sheet having excellent surface quality

    JP2005220430A